Optimization of animal production - Mathur, B. K.; Patel, A. K.; Kachhawa, S.; Kumawat, R. N. (Indian Farming, 2018)
Regular administration of ecbolic powder/liquid from standard company (Replentaâ„¢ / Uteretoneâ„¢ etc.) in prescribed doses for about a week mixed in jaggary starting immediately after -calving to hasten uterine involution. The above package of practices has led to reduction in calving interval and at first -calving by about 6 to 8 months.